Mast cells as novel mediators of reproductive processes - Woidacki, Katja; Jensen, Federico; Zenclussen, Ana C. (Frontiers in Immunology, 2013)
The relationship between mast cells (MCs) and pregnancy is a controversially discussed topic. The presence and quantitative distribution of mast cells in the reproductive tract was confirmed in different species. A phase-dependent oscillation of mast cells during the hormonal regulated oestrous cycle was suggested and on this basis, MCs were assumed to play a positive role in implantation because of their ability to secrete histamine. At later pregnancy stages, they were proposed to have rather a negative role, as their exacerbated activation is associated with pre-term delivery. The present review is intended to provide an overview about uterine MCs that bring to light their unexpected relevance for reproductive processes.